PG F2α Receptor: A Promising Therapeutic Target for Cardiovascular Disease - Zhang, Jian; Gong, Yanjun; Yu, Ying (Frontiers in Pharmacology, 2010)
Prostaglandins (PGs), a group of key lipid mediators, are involved in numerous physiological and pathological processes including inflammation and cardiovascular homeostasis. Each PG acts on its specific and distinct cell surface G protein coupled receptors (GPCR) or peroxisome proliferator-activated receptors (PPARs). Prostaglandin F2aphar receptor (FP) is required for female reproductive function such as luteolysis and parturition. It has recently been implicated in blood pressure regulation, atherosclerosis and other inflammation-related disorders. The emerging role of FP in cardiovascular diseases is highlighted and potential therapeutic translation is discussed in the current review.